Assessing optimism and pessimism about genomic medicine: Development of a genomic orientation scale. Issue 6 (3rd April 2019) - Horrow, Caroline; Pacyna, Joel E.; Sutton, Erica J.; Sperry, Beau P.; Breitkopf, Carmen Radecki; Sharp, Richard R.
Abstract : Efforts to characterize stakeholder attitudes about the implementation of genomic medicine would benefit from a validated instrument for measuring public views of the potential benefits and harms of genomic technologies, which would facilitate comparison across populations and clinical settings. We sought to develop a scale to evaluate attitudes about the future of genomic medicine. We developed a 21‐item scale that examined the likelihood of various outcomes of genomic medicine. The scale was administered to participants in a genomic sequencing study. Exploratory factor analysis was conducted and bivariate correlations were calculated. The genomic orientation (GO) scale was completed by 2895 participants. A two‐factor structure was identified, corresponding to an optimism subscale (16 items, α = 0.89) and a pessimism subscale (5 items, α = 0.63). Genomic optimism was positively associated with a perceived value of genetic test results, higher health literacy, and decreased decisional conflict about participation in a genomic research study. Genomic pessimism was associated with concerns about genetic testing, lower health literacy, and increased decisional conflict about the decision to participate in the study. The GO scale is a promising tool for measuring both positive and negative views regarding the future of genomic medicine and deserves further validation. Abstract :